2005
DOI: 10.1163/1568568053320639
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Gestalt principle of similarity in the watercolor illusion

Abstract: The watercolor illusion presents two main effects: a long-range assimilative color spreading (coloration effect), and properties imparting a strong figure status (figural effect) to a region delimited by a dark (e.g. purple) contour flanked by a lighter chromatic contour (e.g. orange). In four experiments, the strength of the watercolor illusion to determine figure-ground organization is directly compared (combined or pitted against) with the Gestalt principle of similarity both of color and line width. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 14 publications
(29 reference statements)
1
33
0
Order By: Relevance
“…All else being equal, Pinna et al (2001) and Pinna (2005a) demonstrated that the watercolor illusion determines figure-ground segregation more strongly than the Gestalt principles of proximity, good continuation, pragnanz, closure, symmetry, convexity, past experience, and similarity. It was also shown (Pinna, 2005a) that the watercolor illusion includes a new principle of figureground segregation, the asymmetric luminance contrast principle, stating that, all else being equal, given an asymmetric luminance contrast on both sides of a boundary, the region whose luminance gradient is less abmpt is perceived as a figure relative to the complementary more abmpt region, which is perceived as a background. This phenomenal and physical asymmetry across the boundaries makes the figural effect due to the watercolor illusion stronger than in classical figure-ground conditions, and prevents reversibility of figure-ground segregation.…”
Section: Figural Effects In the Watercolor Illusionmentioning
confidence: 99%
“…All else being equal, Pinna et al (2001) and Pinna (2005a) demonstrated that the watercolor illusion determines figure-ground segregation more strongly than the Gestalt principles of proximity, good continuation, pragnanz, closure, symmetry, convexity, past experience, and similarity. It was also shown (Pinna, 2005a) that the watercolor illusion includes a new principle of figureground segregation, the asymmetric luminance contrast principle, stating that, all else being equal, given an asymmetric luminance contrast on both sides of a boundary, the region whose luminance gradient is less abmpt is perceived as a figure relative to the complementary more abmpt region, which is perceived as a background. This phenomenal and physical asymmetry across the boundaries makes the figural effect due to the watercolor illusion stronger than in classical figure-ground conditions, and prevents reversibility of figure-ground segregation.…”
Section: Figural Effects In the Watercolor Illusionmentioning
confidence: 99%
“…They were composed of two different colors: an orange (u′, v′ = 0.231, 0.512; Y = 55 cd m −2 ) inner contour, and purple (u′, v′ = 0.211, 0.375; Y = 20 cd m −2 ) outer contour, presented on a neutral white background (u′, v′ = 0.189, 0.467; Y = 80 cd m −2 ). The WCE is dependent on the luminance contrast between the two borders (Devinck et al 2005;Pinna 2005). Thus, the luminance of the orange contour was higher than that of the purple contour with a luminance ratio of 2.75 corresponding to the higher contrast used in a previous paper; this setting allowed us to obtain a stronger WCE (Devinck et al 2005).…”
Section: Stimulimentioning
confidence: 99%
“…The former is a long-range assimilative spread of color emanating from a thin colored edge -orange -lining a darker chromatic -purple -contour. The latter is a strong enhancement of the unilateral belongingness of the boundaries (Rubin, 1915) where both the figure and the background appear respectively as a bulging object and as a hole with a 3-D volumetric appearance (Pinna, 1987(Pinna, , 2005(Pinna, , 2008aPinna and Grossberg, 2005;Pinna et al, 2001). …”
Section: Introduction: the Watercolor Illusionmentioning
confidence: 99%
“…This figure is published in colour on http://brill.publisher.ingentaconnect.com/content/vsp/spv of surroundedness (Rubin, 1915(Rubin, , 1921 and relative orientation (Bozzi, 1975). It has been shown (Pinna et al, 2003) that the watercolor illusion and its luminance profile along the boundary contours can be considered as a principle of figure-ground segregation distinct and more effective than all the known gestalt principles (see Pinna, 2005Pinna, , 2008a. Given its strong effects, the watercolor illusion is a good tool to investigate how the visual system extracts basic information about the wholeness of an object, and more specifically about its coloration and object-hole effects, starting from its boundaries.…”
Section: Introduction: the Watercolor Illusionmentioning
confidence: 99%
See 1 more Smart Citation